Placental malaria and its effect on pregnancy outcomes in Sudanese women from Blue Nile State - Samia A. Omer; Hagir E. Idress; Ishag Adam; Mutasim Abdelrahim; Ali N. Noureldein; Abdelrahim M. Abdelrazig; Mohammed O. Elhassan; Suad M. Sulaiman (Malaria Journal, 2017)
Abstract Background Malaria infection during pregnancy can result in placental malaria and is associated with adverse pregnancy outcomes particularly among primigravidae. The aim of this study was to assess the prevalence and risk factors for placental malaria and its effect on pregnancy outcomes in Blue Nile state, Sudan. Methods A cross-sectional hospital-based study was conducted consecutively during January 2012–December 2015 in three main hospitals in Blue Nile State, Sudan. At delivery, peripheral and placental blood samples were collected from consenting women. Finger prick blood was used for preparation of peripheral smears and for haemoglobin measurement. Smears were stained with Giemsa and examined microscopically for malaria parasites. Pregnancy outcomes in association to placental malaria were investigated. Results A total of 1149 mothers and their newborns were recruited. The mean (SD) of the age was 23.3 (5.2) years. Detection of malaria parasites was confirmed in 37.8% of the peripheral blood films and 59.3% of the placental films with Plasmodium falciparum as the only species detected. In multivariate analysis, younger age ≤23.2 years old (AOR = 3.2, 95% CI 1.9–5.5; P < 0.001), primiparae (AOR = 3.9, CI 2.1–7.6; P < 0.001), secundiparae (AOR = 2.8, 95% CI 1.5–5.1; P < 0.001, no antenatal care (ANC) visits (AOR = 11.9, 95% CI 7.8–18.1; P < 0.001) and not using bed nets (AOR = 3.5, 95% CI 1.7–6.8; P < 0.001) were risk factors for placental malaria. Education and residence were not associated with placental malaria infection. Placental malaria was significantly associated with maternal anaemia (AOR = 41.6, 95% CI 23.3–74.4; P < 0.001) and low birth weight (LBW) (AOR = 25.2, 95% CI 15.1–41.3; P < 0.001). Conclusion During the study, there was a high prevalence of placental malaria in Blue Nile State-Sudan, as the enhanced control activities were not practiced, leading to adverse pregnancy outcomes, such as maternal anaemia and LBW.